MENGEMBANGKAN JIWA KEWIRAUSAHAAN DI ERA MILENIAL - Budiono Budiono (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2021)
In this millennial era, technological developments are very rapid, changes in economic civilization have unknowingly increased, which was never imagined in the human mind. The industrial revolution 4.0 is a concrete example of this change in economic civilization. Technological developments are realized in industries that combine technological automation with cyber technology. This is the trend of automation and data exchange in manufacturing technology. This includes cyber-physical systems, cloud computing, and cognitive computing. This is both an opportunity and a challenge for millennials, because this millennial generation is better able to take advantage of this opportunity. The methodology used by the researcher (qualitative methodology with an interpretive and critical approach) has the aim of being able to provide meaning in fostering entrepreneurial character in the millennial Muslim generation by using a transcendental and theological-laden divine values ??approach, the researcher has the aim of being able to contribute thoughts that are beneficial for the millennial generation of Muslims in growing and developing Muslims. The integration and moral decadence that has recently been experienced by many generations today must be resisted by the millennial generation to realize the spirit of entrepreneurship guided by Islamic ethical and moral principles.